Letramentos na escola: uma proposta de ensino de língua portuguesa a partir de crônicas literárias - Lima, Daniela dos Reis Santos (2018)
The present text, entitled Letramentos in school: a proposal for the teaching of Portuguese Language from the literary chronicles, presents a proposal for a pedagogical intervention in teaching reading and writing, from textual/discursive genre literary Chronicle, in a class of ninth grade, a public school Hall of Santaluz-Ba. Through a didactic sequence adapted based on Schneuwly and Dolz (2004) and Costa-Hübes (2009), aim the development of skills in students, writers and readers based on the perspectives of literacy. In this sense, we support the theoretical constructs of Street (1995), Soares (1998; 2002), Rojo (2009), Cosson (2016), Lajolo (2001), Petit (2009), the PCN of Portuguese Language, third and fourth cycles (1998), Sá (1985), Cândido (1992; 1995), Freitas ( 2011), Antunes (2010; 2016), among others. This is a qualitative and ethnographic based character, which brings answer the following question: in what way is the development of a didactic sequence, with a focus on textual/discursive genre literary Chronicle, may contribute to the skills development readers and writers, in Portuguese Language, based on the perspectives of the literacy? So, in addition to the genre, literary literacy Chronicle, we insert in the search using multimodal languages, as the photography, with the appropriation, in the framework of school practices commonly used by students in the times today. The survey results show that it is possible to enlarge the communicative competence of students, as well as critical reflection about the world and themselves, through the literacy, especially the literary, highlighting the chronic and your feature humanizing